Separation anxiety disorder in adult patients with obsessive-compulsive disorder: prevalence and clinical correlates - Franz, A. P.; Rateke, L.; Hartmann, T.; McLaughlin, N.; Torres, A. R. [UNESP]; Rosário, M. C. do; Filho, E. C. M.; Ferrão, Y. A. (Elsevier B.V., 2015)
Objective: Individuals with obsessive-compulsive disorder (OCD) and separation anxiety disorder (SAD) tend to present higher morbidity than do those with OCD alone. However, the relationship between OCD and SAD has yet to be fully explored.Method: This was a cross-sectional study using multiple logistic regression to identify differences between OCD patients with SAD (OCD + SAD, n = 260) and without SAD (OCD, n = 695), in terms of clinical and socio-demographic variables. Data were extracted from those collected between 2005 and 2009 via the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders project.Results: SAD was currently present in only 42 (4.4%) of the patients, although 260 (27.2%) had a life-time diagnosis of the disorder. In comparison with the OCD group patients, patients with SAD + OCD showed higher chance to present sensory phenomena, to undergo psychotherapy, and to have more psychiatric comorbidities, mainly bulimia.Conclusion: In patients with primary OCD, comorbid SAD might be related to greater personal dysfunction and a poorer response to treatment, since sensory phenomena may be a confounding aspect on diagnosis and therapeutics. Patients with OCD + SAD might be more prone to developing specific psychiatric comorbidities, especially bulimia. Our results suggest that SAD symptom assessment should be included in the management and prognostic evaluation of OCD, although the psychobiological role that such symptoms play in OCD merits further investigation. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Obsessive-compulsive disorder; Separation anxiety disorder; Comorbidity; Anxiety; Diagnosis; Epidemiology